Severe pediatric Mycoplasma pneumonia as the cause of diffuse alveolar hemorrhage requiring veno-venous extracorporeal membrane oxygenation: A case report - Zhang, Xinjuan; Yu, Yanping (Frontiers in Pediatrics, 2023)
Background: Diffuse alveolar hemorrhage (DAH) is an acute life-threatening disease often associated with immunocompromised patients and systemic disorders, such as infections, vasculitis, and toxins. Mycoplasma pneumoniae is one of the most common causes of community-acquired pneumonia in children, which rarely causes respiratory failure and fulminant disease; However, a rapid progression may occur in some patients. Mycoplasma pneumonia-associated DAH is rare. Case Presentation: We report a case of severe pediatric mycoplasma pneumonia in an immuno-competent child. This patient's condition progressed rapidly, with severe lung lesions associated with pleural effusion, coagulopathy, diffuse alveolar hemorrhage, and severe respiratory distress and required ventilator and veno-venous extracorporeal membrane oxygenation (VV-ECMO) support. She was discharged upon successful treatment. Conclusion: Diffuse alveolar hemorrhage associated with Mycoplasma pneumoniae in children is very rare, and clinicians should be aware of the potential rapid onset of the disease. Early detection and diagnosis are very important. The main treatment measures include anti-infection and active supportive treatment, including mechanical ventilation and ECMO.